Web-Based Project Documentation Repository System - Al Sbou, Ali Mousa Eid (2009)
The purpose of this study is to explain the need for a web-based application to provide the information technology student's projects with the necessary and essential resources. The proposed system provides students with an efficient system to search and retrieve about the previous information technology master projects with the information on the topics of projects, list and details of submitted projects. Project Document Repository System supports unified access, efficient documents utilization and management through a simple to use, standard web browser interface. The study identifies the main features and functionalities to manage and organize project's documents. The proposed prototype will make the process of storing, searching and retrieval of the project document become more effective, easy and faster. The prototype is tested and evaluated to achieve the objectives of the study.